Shaping Ethylene Response: The Role of EIN3/EIL1 Transcription Factors - Dolgikh, Vladislav A.; Pukhovaya, Evgeniya M.; Zemlyanskaya, Elena V. (Frontiers in Plant Science, 2019)
EIN3/EIL1 transcription factors are the key regulators of ethylene signaling that sustain a variety of plant responses to ethylene. Since ethylene regulates multiple aspects of plant development and stress responses, its signaling outcome needs proper modulation depending on the spatiotemporal and environmental conditions. In this review, we summarize recent advances on the molecular mechanisms that underlie EIN3/EIL1-directed ethylene signaling in Arabidopsis. We focus on the role of EIN3/EIL in tuning transcriptional regulation of ethylene response in time and space. Besides, we consider the role of EIN3/EIL1-independent regulation of ethylene signaling.